Columbite-rich multiphase TiO2 nanoceramic with superior mechanical and dielectric properties. Issue 9 (August 2021) - Liu, Bing; Sun, Lei; Wu, Yingju; Zhang, Yang; Li, Zihe; Chen, Junyun; Xie, Chenlong; Huang, Quan; Ma, Mengdong; Luo, Kun; Gao, Yufei; He, Julong; et al.
Highlights: A series of columbite-rich multiphase TiO2 nanocrystalline ceramics were fabricated through high-pressure and high-temperature method. The TiO2 ceramic containing 85.25 % columbite phase has a considerable high Vickers hardness of 12.76 GPa. The columbite-rich TiO2 ceramic shows a colossal permittivity (∼8000) and low loss (∼0.2) at 1 kHz and room temperature. Abstract: Columbite-rich multiphase TiO2 nanoceramics with outstanding mechanical and dielectric properties were successfully prepared through high-pressure sintering by using anatase-type TiO2 as precursor. High-pressure sintering combined with phase transformation assisted consolidation can effectively refine the grain size of the recovered samples. This process is conducive to obtain nanocrystalline columbite-rich TiO2 ceramics with excellent performance. The highest hardness is approximately 12.76 GPa, which is 2.5 times higher than that of ordinary coarse-grained ceramics. The effect of columbite phase on the hardness of multiphase ceramics is discussed. The columbite-rich TiO2 ceramic shows a colossal permittivity (∼8 × 10 3 ) and low loss (∼0.2) at 1 kHz and room temperature, which are superior to that of undoped rutile polycrystalline ceramics. This ceramic shows a steadier frequency-dependent dielectric permittivity and loss than rutile TiO2 crystal. These results enrich the fundamental knowledge of columbite-rich TiO2, thereby enabling the exploitation of new applications.